Representation of Partisan, Territorial, and Institutional Interests in Second Chambers: Evidence from the German Bundesrat and its Committees. Issue 2 (14th November 2019) - Finke, Patrick; Müller, Markus M; Souris, Antonios; Sturm, Roland
Abstract: Revisiting the longstanding debate on interest representation in federal second chambers, this article investigates the influence of partisanship vis-à-vis territorial and other interests such as institutional concerns on deliberations. We argue that committees as the actual place of policy- and decision-making provide an instructive approach to understand interest representation in second chambers, just as in first chambers. For the empirical part of our study, we focus on the German Bundesrat and its committees. Based on the protocols of their meetings, we developed a new dataset that contains information on more than 51, 000 roll call votes, the largest-ever empirical basis to study interest representation and decision-making in the Bundesrat . Above all, we find that partisanship plays a role, yet a minor one. The representatives prioritize individual or joint sub-state interests over their political party affiliations, just like the founding fathers of the Federal Republic have envisaged it in the German constitution.